Hospital Dentistry Approach to a Patient with Mucormycosis treated with Amphotericin B: Case Report - Gomes Júnior, George Matos Ferreira; Falcão, Ivyna Maria Cardins; da Silva, Carla Welch; Maia, Isaac Müller de Sousa; Lobo, Camila de Oliveira; Estácio, Luanda Ashley Menezes; Gusmão, Jonas Nogueira Ferreira Maciel; Santos, Daniel Facó da Silveira; Santos, Eliardo Silveira (Brazilian Journal of Case Reports, 2025)
This study addresses rhino-orbito-cerebral mucormycosis, a serious and opportunistic fungal infection, especially in immunosuppressed patients, such as those with type II diabetes mellitus. The study highlights the importance of a multidisciplinary approach in diagnosing and treating this condition, emphasizing collaboration between medical and dental specialties. Through a clinical case, it demonstrates how early and coordinated intervention can minimize the devastating consequences of the infection, underscoring amphotericin B, especially in its liposomal form, as the preferred treatment and the need for surgical debridement. The study reinforces the vigilance and early recognition of mucormycosis symptoms, particularly in patients with risk factors such as uncontrolled diabetes, illustrating the importance of integration between different medical fields in managing complex diseases.